A Case Report of Radiation Therapy as Definitive Treatment for Desmoid Tumor in a Young Girl - Rafiq Sulistyo Nugroho; Irma Darinafitri; Eviana Norahmawati; Istan Irmansyah Irsan; Satria Pandu Persada Isma (http://dharmais.co.id/, 2023)
Introduction: Desmoid tumor is a benign growth that can exhibit aggressiveness and various patterns, resulting in a wide range of management methods. These methods include observation to active interventions, such as surgery, radiation, and systemic therapy. Therefore, this case report aimed to present the role of radiation therapy for desmoid tumors in a young girl who refused limb amputation to preserve the organ.Case Presentation: This study presented the case of a 13-year-old girl with a vast and painful desmoid tumor in the left upper arm. Magnetic resonance imaging (MRI) on the left shoulder showed an 8 x 9 x 17 cm solid soft tissue mass on the left deltoid muscle with the necrotic component that expands to adjacent cutaneous and subcutaneous tissue. In this case, the left humerus attaches to the deep brachial artery and vein. Previous pathological studies with immunohistochemicals showed desmoid fibromatosis. A multidisciplinary team discussion led to the selection of, radiotherapy for treatment because of tumor localization and proximity to the critical structure. Radiation was also selected as the definitive therapy of choice with the aim of local control and organ preservation. Furthermore, the radiation dose was 56 Gy in 2 Gy per fraction over six weeks. After six months of follow-up, the patient reported pain relief, improved range of motion, and reduced tumor size.Conclusion: Radiotherapy reduced desmoid tumor size and improved symptoms without compromising organ function in young girls.